Exploration of Indole Acetic Acid (IAA) Producing Fungi from Non-organic Carrot Rhizosphere as Biostimulant - Ramadhan, Akhmad Andika; Purwantisari, Susiana; Rasyid, Rido Baharudin Ar (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to isolate and characterize fungi from the rhizosphere of carrots grown in non-organic systems that potentially produce indole-3-acetic acid (IAA), and to evaluate their biostimulatory potential in supporting environmentally friendly agriculture. The methods employed included rhizospheric sample collection from non-organic carrot fields, fungal isolation and purification using PDA media, morphological identification, as well as qualitative screening and spectrophotometric quantification of IAA production using Salkowski reagent. The results revealed six fungal isolates capable of producing IAA, namely Rhizopus stolonifer, Rhizopus oryzae, Trichoderma longibrachiatum, Trichothecium roseum, Pythium aphanidermatum, and Pythium inflatum, with varying levels of IAA production. Among these, R. oryzae produced the highest IAA concentration at 46.8 ppm, followed by P. aphanidermatum (41.8 ppm), T. longibrachiatum (27.3 ppm), P. inflatum (24.5 ppm), R. stolonifer (18.4 ppm), and T. roseum (17.9 ppm). These findings suggest that rhizospheric fungi from the non-organic carrot rhizosphere hold promising potential as IAA-producing bioagents to support sustainable and environmentally friendly agricultural practices.